Assessment strategies for work related learning in industrial clothing design and construction. A case of two polytechnic colleges in Zimbabwe. - Masina, Rumbidzayi; Mukaro, Joe Phaeton; Kaifa, Jane (Academic Research Centre, 2022)
Industrial Clothing Design and Construction (ICDC) is a practical course that requires students to acquire work experience during their training in preparation for the world of work. The purpose of this study was to explore the assessment procedures for Work Related Learning (WRL) used in ICDC in the Polytechnic Colleges in Zimbabwe. A qualitative research approach utilising a case study research design was used. Research sites and participants were purposively sampled. Two Polytechnic Colleges and three Host Industries were selected. Eight lecturers, three industrial supervisors, two external assessors, two policy makers and ten students were purposively selected for this study. Data were collected through interviews with lecturers, industrial supervisors, external assessors and policy makers. Focus group discussions with students and review of documents used for assessment during WRL were also used for data collection. Data were analysed using thematic data analysis technique. The findings revealed that there are no clearly defined policies on WRL for ICDC. The processes involved in assessment during WRL were considered as haphazard and inadequate. This study therefore recommends intensive professional development workshops aimed at improving the way assessment is realised in Polytechnic Colleges in Zimbabwe. Similar workshops can also be extended to other stakeholders who are in the assessment matrix. This will have an impact on policy formulation for WRL and the realisation of education 5.0 through research and innovation.